If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -3 = -12x + 10 Reorder the terms: -3 + X = -12x + 10 Reorder the terms: -3 + X = 10 + -12x Solving -3 + X = 10 + -12x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + X = 10 + 3 + -12x Combine like terms: -3 + 3 = 0 0 + X = 10 + 3 + -12x X = 10 + 3 + -12x Combine like terms: 10 + 3 = 13 X = 13 + -12x Simplifying X = 13 + -12x
| x^2+y^2+x+y-96=0 | | 36=-0.5x^2+108 | | 2y+7=-2y-1 | | 4/9/x=12 | | (2x+3y-4)dx+(-4x+y+1)dx=0 | | 7x-3.5=-4x-3.2 | | 2-2x=6-1x | | 5/9÷15/36 | | x^5-125x^3+484x=0 | | 20-8.50= | | x^2-2mx+8m=0 | | 27=6+3y | | -10=u/5-5 | | x(5x^2-15x-1)=3 | | X+6x=100 | | 6a+4b-5a-b+3= | | (x^2)/3=7/2 | | x^2/3=7/2 | | 9(x+11)=-6(x-20) | | 3(a+2)+4(a+5)= | | -k-3+k^3-3k^2=0 | | (x-1)/4-3=(x-7)/3 | | 25=625-50x | | -9u+7=24u-4 | | P(x)=x^3-25x+12 | | 4a+b+3a+2b= | | (2x+y)dx+(x+y+1)dy=0 | | 17-3z=z-1 | | 5p=5p-15 | | 980n=361 | | 308-11x=8x | | 575980x=130361 |